2020
DOI: 10.7759/cureus.8287
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Unresectable Malignant Granular Cell Tumor With Response to Pazopanib

Abstract: Malignant granular cell tumors (MGCTs) are rare and aggressive variants of granular cell tumors. They usually involve the head and neck region, skin and soft tissues. There are no standard therapeutic guidelines for management; however, surgical resection, whenever feasible, is considered to be first line. We report a patient with recurrent unresectable MGCT of lower lip who responded to pazopanib monotherapy. This drug has been recently approved for the treatment of advanced soft tissue sarcomas. It is a pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Amongst these, 75 articles that fulfilled the above criteria according to their abstract or tittle were identified. After reviewing the full texts of these 75 articles, 10 articles were finally selected (Figure 2) [20][21][22][23][24][25][37][38][39][40]. The most common target systemic therapy used in GCTs according to this review of the literature was pazopanib, (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Amongst these, 75 articles that fulfilled the above criteria according to their abstract or tittle were identified. After reviewing the full texts of these 75 articles, 10 articles were finally selected (Figure 2) [20][21][22][23][24][25][37][38][39][40]. The most common target systemic therapy used in GCTs according to this review of the literature was pazopanib, (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Five patients had received previous systemic therapy, with limited benefit in terms of progression-free survival while no objective responses were detected. Previous treatments were as follows: three patients received chemotherapy (the different schemes administered were carbo-platin/paclitaxel + cetuximab, gemcitabine/docetaxel, doxorubicin/ifosfamide) [23,24,38] and no responses were reported, one patient received dasatinib progressing after two months, and one patient received smoothened inhibitor, after progression a PI3K inhibitor was administered with disease control lasting nine months [21].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have reported success using the sarcoma treatment pazopanib and some recommend adjuvant radiotherapy. 28,29 Owing to the rarity of malignant GCTs, no randomized clinical trials have been performed. Benign GCTs have an excellent prognosis with complete surgical excision regarded as curative.…”
Section: Radiology Treatment and Prognosismentioning
confidence: 99%
“…Chemotherapy and adjuvant radiotherapy have a disputed role in treating malignant GCTs and metastatic disease. Some authors have reported success using the sarcoma treatment pazopanib and some recommend adjuvant radiotherapy 28,29 . Owing to the rarity of malignant GCTs, no randomized clinical trials have been performed.…”
Section: Radiology Treatment and Prognosismentioning
confidence: 99%